A reinvenção da cidade: a transformação das ruas e o reordenamento da vida na cidade de Vitória/ES, 1890-1928 - Ferreira, Gilton Luis (2016)
The reinvention of the city - metonymy of urban modernization and consequence of modernity, ideology of progress and technical rationality — radically changed the forms of spatial organization, social relationships, habits and customs of life in the urban universe of the Western world. When articulating categories of distinct analysis such as space and society in the long term and shorter clippings, the urban way of life as category of analysis, and the city as a research subject inscribed in historiography are shaped. In order to explain how the changes occurred in the urban space of the city of Vitória, state capital of Espírito Santo, influenced the adoption of new social practices and appropriation of public spaces by its population, the urban instruments that made the reorganization of collective life possible from 1890 to 1928, are identified that is, from the year of the publication of the first Municipal Code of Postures of the city of Vitória — the republican period — until the end of the government of the President of the State Florentino Avidos — period when sources revealed a significant amount of physical and social changes in the city, interpreted as the period of its reinvention.